Analysis of Vocational School Development Based on Regional Potential Using Principal Component Analysis (PCA) - S., Saripudin; Budiyanto, Ida Bagus (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2020)
This study aims to analyze the development of Vocational High School (SMK) based on regional potential in Cimahi City, Indonesia. This study is descriptive research. This study was conducted in Cimahi City, West Java Province, Indonesia. The population and sample of this study were all the potentials of the region and the industrial fields in the City of Cimahi, West Java and the fields/programs/competencies of SMKs in the City of Cimahi. Data in this study were collected using documentation, interview and observation methods. The Principle Component Analysis (PCA) was used as the method of analyzing regional potentials using Minitab Statistical Software version 14. Based on the results of this study it was found that the development of Vocational High Schools is based on regional potential in Cimahi City and based on the analysis of Vocational Development Levels in Cimahi City by using the PCA analysis method based on indicators education such as Total Population Ages 16-18, Student Ratio per School, Student Ratio per Class, Student Ratio per Teacher, and Gross Participation Rate (GPR) in 3 (three) Districts of Cimahi City found that the lowest PCA 1 for the three districts is in South Cimahi District (-1026.02). This means that the priority location I for the development of SMK is South Cimahi District. It is then followed by Central Cimahi Subdistrict (-644.19) which becomes priority location II for the development of SMK. And Priority III is the District of North Cimahi (-435.5). With these findings, the Office of Education, especially in the area of Vocational Secondary Education in the Cimahi City, West Java, should pay attention to the development of vocational schools which requires careful study in establishing vocational schools based on the potential of the region.